Case report: Ectopic corpus cavernosum presented as bladder tumor in a 3-year-old boy - Chai, Jia-gui; Zhao, Yan-liang; Yin, Si-fan; Yin, Zhi-yuan; Zhao, Shen-zhao; Feng, Run-lin; Ke, Chang-xing (Frontiers in Oncology, 2024)
Background: Ectopic tissue is rarely found in the bladder for adults. Currently, there have been reports of ectopic prostate and colon tissue in the bladder. These ectopic tissues are manifested as a bladder mass and cause lower urinary tract symptoms. However, the ectopic corpus cavernosum in the bladder has never been reported, and its clinical characteristics and treatment have not been explored yet.Case summary: A 3-year-old boy was admitted to the hospital due to 1 month of urinary frequency. The physical examination was unremarkable. Urine analysis from other hospitals showed an elevated urine white blood cell count of 17.9/ul. In addition, ultrasound indicated a possible bladder mass. CT and MRI showed a well-margined lesion (1.9◊1.9 cm) in the bladder trigone. Through preoperative imaging, we diagnosed a bladder tumor (inclined towards benign). The transurethral resection of the bladder tumor was performed. Unfortunately, the surgery was unsuccessful due to the difficulty in removing the excised tissue through the urethra. Subsequently, bladder incision and tumor resection were performed. The tumor was successfully removed. Surprisingly, the postoperative pathology showed that the tumor tissue was corpus cavernosum. The pathological diagnosis was ectopic corpus cavernosum in the bladder. No complications were found after the operation, and no recurrence was observed during follow-up.The ectopic corpus cavernosum in the bladder has never been reported for children, which is presented as a benign tumor with rapid proliferation and large size. Surgery is recommended. However, the transurethral resection of bladder tumors is difficult to perform due to narrow urethra and limited surgical instruments. Bladder incision and tumor resection may be preferred.Case report: Ectopic corpus cavernosum presented as bladder tumor in a 3-year-old boy